APPLICATION OF A MATHEMATICAL MODEL FOR THE GENERATION OF SEPARATE ELEMENTS OF A STEGANOGRAPHIC SYSTEM IN A HIGHER EDUCATION INSTITUTION (Computer systems and information technologies, 2023)
The article presents the method of generating separate elements of the steganographic system based on the combination of cryptography and steganography methods, which makes it possible to increase the level of information protection and develop more effective new non-traditional methods of ensuring information security in the global network. Considering the constant development and improvement of computer cryptography and steganography methods, the study of this particular area of steganoanalysis is the most relevant. It is proposed to apply the method of replacing the least significant bits (LSB method), because it, in combination with the RSA cryptographic algorithm, allows to ensure a high level of information security and the speed of embedding and extraction of a large amount of information.The practical value lies in the ability to quickly generate steganographic containers and ensure reliable encryption and decryption of hidden information in them. At the stage of experimental research, the proposed method of replacing the younger bits was compared with other methods that could be used to generate individual elements of the steganographic system. According to research results, the LSB method has clearly confirmed its effectiveness. The results of the experiment showed the high stability and quality of the received data encryption and decryption method when sending it through an open communication channel (e-mail).
Keywords: steganographic system; cryptography; encryption; decryption; steganoanalysis; fractals; RSA; LSB